Copper removal from sediment microbial fuel cells with cathode with added slow-release oxygen beads: Performance, power output and microbial communities. (15th December 2022) - Lin, Chi-Wen; Ho, Chia-Yun; Zhu, Ting-Jun; Liu, Shu-Hui
Abstract: Sediment microbial fuel cells can generate electrons by degrading organic contaminants in a sediment environment, promoting the migration of copper ions from the sediment to the cathode. They can thus be used to remove copper ions from sediment. Biochar-based oxygen-releasing beads were developed and added to the cathode in sediment microbial fuel cells to treat copper-contaminated sediment. The slow release of O2 from the oxygen-releasing beads and the adsorption of copper ions by the biochar increased the output voltage, degradation of organic pollutants and removal of copper ions by the sediment microbial fuel cells. The power density of the sediment microbial fuel cell with 10 g beads at the cathode was 66.2 mW/m 2, which is 2.3 times that of without oxygen-releasing beads. The recovery percentage of copper ions in sediment microbial fuel cells with oxygen-releasing beads was 51.2%, which is 1.4 times the value, 34.8%, for sediment microbial fuel cell without beads. Therefore, adding oxygen-releasing beads improved the voltage output of the sediment microbial fuel cell and accelerated the migration of copper ions, solving the problem of low mass transfer in the sediment. Accordingly, significant amounts of copper compounds are formed on the cathode and surfaces of biochar-based oxygen-releasing bead, confirming that this technology can be effectively used to remediate heavy metal-contaminated sediment and to generate electricity. Graphical abstract: Image 1 Highlights: ․Oxygen-releasing beads slowly release O2 and effectively adsorb Cu 2+ . ․Single-medium sediment microbial fuel cell increases anaerobic respiration. ․Power of microbial fuel cell is improved by adding oxygen-releasing beads to cathode. ․Cu compounds on cathodic and oxygen-releasing bead surfaces confirmed Cu reduction.